FIXED POINT THEOREMS FOR KANNAN TYPE CYCLIC WEAKLY CONTRACTIONS - Karapinar, E.; Nashine, H. K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this article, we introduce the notion of Kannan Type cyclic weakly contraction and derive the existence of fixed point theorems in the setup of complete metric spaces. Our main theorems extend and improve some fixed point theorems in the literature. Examples are given to support the usability of the results.